Republic of Belarus : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Belarus. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the Belarusian economy is recovering after two years of recession, helped by better policies, a more favorable external environment, and stronger domestic demand conditions. In 2017Q3, the economy grew by 1.7 percent year-on-year, amid household consumption boosted by strong wage growth and recovering investment. The current account deficit has narrowed, reflecting growth in services exports, as well as recession and real exchange rate adjustment in 2015-16. Medium-term growth is expected to be about 2 percent, limited by negative demographics, weak credit conditions, and lagging competitiveness under the state-centric economic model.